Background levels and brain organoid impact of RF field exposure in a healthcare environment - Hernández, José A.; Rosca, Andreea; Suárez, Samuel; Coronel, Raquel; Suarez, Oscar J.; Peran-Ramos, Paula; Marina, Pablo; Rabassa, Luis E.; Mateos, Patricia; Liste, Isabel; López-Alonso, Victoria; Torres-Ruiz, Monica; et al. (Frontiers in Antennas and Propagation, 2024)
Introduction: This study is an introduction to the empirical and impact evaluation of radiofrequency electromagnetic field (RF-EMF) radiation exposure in a healthcare environment, focusing on an indoor microenvironment. It explores the expression of various genes associated with cellular responses, cell proliferation, senescence, and apoptotic cell death. The assessment analyzes current personal mobile communications (2G-5G FR1), providing a clear understanding of RF-EMF exposure and compliance with regulatory limits. Methods: The signals from different wireless communication systems at Hospital Universitario de Canarias (HUC) in Tenerife, Canary Islands, Spain, were examined in 11 locations. Four measurement campaigns were performed with frequency-selective exposimeters (PEMs) and an EME Spy 200 MVG, and experimental electric field values were compared as a long-term exposition. The frequency with the highest contribution (2.174 V/m) observed (1840 MHz) in UMTS was selected for biological effects evaluation. Results: The study focuses on four locations with the highest exposure to communication systems (downlinks), analyzing the results to verify compliance with regulations that ensure the safety of patients, the general public, and healthcare workers. LTE B20 (DL), GSM+UMTS 900 (DL), GSM 1800 (DL), UMTS 2100 (DL), and LTE B7 (DL) exhibited relatively higher E/m values throughout the campaigns, and these values consistently remained below the ICNIRP reference levels, signifying a consistently low level of exposure. In addition, this work presents the biological effects on neural stem cells (NSCs) using 3D brain organoids (BOs) exposed to RF signals in a validated and commercial experimental setting: the Gigahertz Transverse Electromagnetic cell (GTEM). The GTEM allows for the creation of homogeneous field electromagnetic fields in a small, enclosed setting and guarantees exposure conditions in a wide range of frequencies. BOs are an in vitro 3D cell-culture technology that reproduces the cellular composition and structure of the developing brain. Analyzing the expression of several genes associated with cellular responses, cell proliferation, senescence, and apoptotic cell death, we found that exposure of BOs at 1840 MHz did not affect mRNA expression in brain genes related to apoptosis or senescence. However, a decrease in gene expression for cell proliferation and cell activity markers was observed during the differentiation stage of BOs. Discussion: The discussion emphasizes the coexistence and evolution of various heterogeneous networks and services throughout the four measurement campaigns. Across all measured results, the levels of the obtained E-field were consistently well below the exposure limits set by internationally accepted standards and guidelines. These obtained values have been established in order to consider their potential effects on cell proliferation and cell activity, especially in differentiating biological organisms. Consequently, the results obtained and the methodology presented could serve as a foundational framework for establishing the basis of RF-EMF assessment in future heterogeneous 5G developments, particularly in the millimeter wave (mmWave) frequency range, where the forecast is for massive high-node density networks.